Genetic diversity and morphological variability in Polygonum aviculare s.l. (Polygonaceae) of Iran - Mosaferi, Samaneh; Sheidai, Masoud; Keshavarzi, Maryam; Noormohammdai, Zahra (Phytotaxa, 2015)
A molecular investigation was carried out on the variable species Polygonum aviculare using 109 plants from 12 Iranian populations. ISSR molecular markers were used for genetic study. AMOVA and Gst analyses revealed a high genetic variability both within and among populations. Mantel test showed positive significant correlation between genetic and geographical distance of populations. Structure and K-Means clustering revealed stratification ingenetic characteristics of accessions. Networking and reticulation analyses showed some degree of gene exchange among populations. Consensus tree based on morphological and genetic data separated some of these populations from the others suggesting the existence of new taxa within this species.